Diseño de la estructura productiva de la empresa Hojaldres y Delicias Divali (2000)
This degree project was carried out at the request of the company DIVALI Ltda, in which it is intended to increase the productive capacity of the plant, this in order to meet the needs of a new market segment, in which it is intended to distribute the company products to the general public, in chain supermarkets in the city of Santafé de Bogotá, a market segment that the company does not currently work with.